Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

The decreased competition in expanding versus mature juniper woodlands is counteracted by adverse climatic effects on growth - Gimeno, Teresa E.; Pías, Beatriz; Martínez-Fernández, Jesús; Quiroga, David L.; Escudero, Adrián; Valladares, Fernando (European Journal of Forest Research, 2011)
World-wide deforestation is being reversed in Mediterranean continental areas, where abandonment of traditional practises favours the expansion of valuable habitats, like Juniperus thurifera woodlands. We hypothesised that pre-existing trees facilitate establishment in expanding woodlands, whereas in mature woodlands, competition leads to patch disaggregation. We compared the imprint of these processes on growth, demographic and spatial structure of expanding and mature J. thurifera woodlands. We selected plots where we geopositioned, aged and quantiﬁed the morphological characteristics of all trees. In the mature woodland, trees arranged in clumps and randomly in the expanding woodland. Competition negatively affected growth, was greater in the mature woodland and led to disaggregation of juvenile clumps. Differences in growth between the mature and the expanding woodland disappeared in climatically unfavourable years, suggesting that adverse climate constrains growth more in expanding than in mature woodlands. We suggest that change in the dispersal agents and a decrease of facilitation underlay differences in spatial patters between the expanding and the mature woodland. Observed effective recruitment in less than 30 years into the expanding woodland evidenced that propagule arrival and sapling survival do not constrain woodland expansion. Furthermore, growth of juveniles established in these new areas is favoured by reduced intraspeciﬁc competition. However, we expect growth in expanding woodlands to be negatively impacted by climate change. We conclude that under current global change scenario, conservation of J. thurifera woodlands is favoured by changes in land use, but greater frequency and severity of drier than usual episodes could hamper natural reforestation.
Keywords: Juniperus thurifera; Plant–plant interactions; Radial growth; Spatial pattern; Woodland expansion; Woodlandisation

Asociación espacial de especies leñosas dominantes a lo largo de gradientes ambientales: estudio de la regeneración de un bosque mediterráneo continental - Granda, Elena; Valladares, Fernando; Escudero, Adrián; de la Cruz, Marcelino; Gimeno, Teresa E; Matesanz, Silvia; Pías, Beatriz; López, David (V Congreso Forestal Español, 2009)
Los fenómenos de competencia y facilitación entre plantas presentan importantes variaciones según la etapa de vida y fisiología de las especies que interactúan, dependiendo además del estrés abiótico e interacciones indirectas. Dada la importancia del análisis espacial en el entendimiento de la estructura y funcionamiento de los ecosistemas, hemos llevado a cabo un estudio descriptivo en localidades contrastadas de bosque mediterráneo continental en el Parque Natural del Alto Tajo (Guadalajara). Se ha registrado el clima de cada localidad y los patrones espaciales de individuos de las cuatro especies dominantes (Quercus ilex subsp. ballota, Quercus faginea, Pinus nigra subsp. salzmannii y Juniperus thurifera). Los propósitos son: determinar patrones de agregación, repulsión o distribución al azar; establecer si dicha distribución está relacionada espacialmente con las características de cada localidad e identificar si los patrones muestran diferencias entre especies. Los resultados indican grandes diferencias entre las cuatro especies. Encontramos que en conjunto, la frecuencia de juveniles era mayor bajo la protección de otros individuos, existiendo diferencias según las especies beneficiarias y benefactoras, y tipo de bosque considerado. Las explicaciones varían desde la facilitación mediada por la mejora en las condiciones microclimáticas hasta una interacción positiva debida al efecto percha o protección frente a los herbívoros. Se discuten las implicaciones de estos resultados para la regeneración natural.
Keywords: Interacciones; Juniperus thurifera L.; Pinus nigra J.F.Arnold subsp. salzmannii (Dunal) F; Quercus faginea Lam.; Quercus ilex subsp. ballota (Desf) Samp.; reclutamiento

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T.; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover